2017
DOI: 10.1007/s11187-017-9946-7
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and local economic resilience: the impact of institutional hysteresis in peripheral places

Abstract: This article examines how the legacies of the past in peripheral post-industrial places serve to shape current and future entrepreneurial activity, and with it local economic resilience. Drawing on in-depth qualitative interviews with key regional stakeholders, the article reveals how peripheral post-industrial places are constrained by their histories. This is found to be manifest in different ways, such as low aspirations, generational unemployment and a loss of identity which are in turn compounded by negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 70 publications
1
43
0
1
Order By: Relevance
“…Such constructions of places offer us a theoretical lever because different identities may clash and be resistant to change. Gherhes, Vorley, and Williams () described how depleted communities, peripheral postindustrial places can be caught up in vicious circles of suboptimal development trajectories. Their histories shape informal institutions, forming place identities that deter change, especially entrepreneurial change.…”
Section: Introductionmentioning
confidence: 99%
“…Such constructions of places offer us a theoretical lever because different identities may clash and be resistant to change. Gherhes, Vorley, and Williams () described how depleted communities, peripheral postindustrial places can be caught up in vicious circles of suboptimal development trajectories. Their histories shape informal institutions, forming place identities that deter change, especially entrepreneurial change.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, micro-businesses operating in PPIPs face 'additional costs' including limited access to higher-skilled labour and a 'closed' business environment, factors that are compounded by the negative perceptions stemming from a stigmatisation of PPIPs that can further stymie growth. Building on Gherhes et al (2018) the paper explores how these 'additional costs' facing established micro-businesses manifest as a product of institutional hysteresis that is constraining entrepreneurial ambition in PPIPs. Second, the findings emphasise that micro-businesses growth is contingent on the ambition and capabilities of the OME, and therefore developing leadership and management capacity is essential for the growth of micro-businesses.…”
Section: Ppipmentioning
confidence: 99%
“…Moreover, while much of the research on peripherality has been carried out at the regional level, the local, intra-regional level remains less explored (Trettin and Welter, 2011;Huggins et al, 2017). For example, Gherhes et al (2018) have shown how, in PPIPs, institutional hysteresis at the local level constrains entrepreneurship by limiting entrepreneurial ambition and aspirations. However, how such a local socio-institutional context influences established businesses is yet to be explored.…”
Section: Entrepreneurship In the Post-industrial Peripherymentioning
confidence: 99%
See 2 more Smart Citations